First records of Micranurida and Philotella (Collembola, Neanuridae, Pseudachorutinae) from China with the description of three new species - Gao, Yan; Palacios-Vargas, José G.; Arango, Angela; Bu, Yun (Zootaxa, 2024)
The genus Micranurida Börner, 1901 and Philotella Najt & Weiner, 1985 are reported from China for the first time, with the following new species Micranurida hunanensis sp. nov. from the Hunan province, Central China, Philotella glabrasterna sp. nov. and Philotella subiasi sp. nov. from the Hebei province, North China.